A Participatory, Mixed Methods Approach to Define and Measure Partnership Synergy in Long‐standing Equity‐focused CBPR Partnerships. Issue 3 (3rd August 2020) - Coombe, Chris M.; Chandanabhumma, P. Paul; Bhardwaj, Prachi; Brush, Barbara L.; Greene‐Moton, Ella; Jensen, Megan; Lachance, Laurie; Lee, S.Y. Daniel; Meisenheimer, Melanie; Minkler, Meredith; Muhammad, Michael; Reyes, Angela G.; et al.
Abstract : Abstract: Understanding what contributes to success of community‐based participatory research (CBPR) partnerships is essential to ensuring their effectiveness in addressing health disparities and health inequities. Synergy, the concept of accomplishing more together than separately, is central to partnership effectiveness. However, synergy specific to long‐standing, equity‐focused CBPR partnerships has not been closely examined. To address this, we defined and developed measures of partnership synergy as one dimension of a participatory mixed methods study, Measurement Approaches to Partnership Success (MAPS), to develop a validated instrument to measure success in long‐standing CBPR partnerships. Framed by a conceptual model and scoping literature review, we conducted in‐depth interviews with a national panel of academic and community experts in CBPR and equity to develop partnership synergy measures. Items were refined through an iterative process, including a three‐stage Delphi process, comparison with existing measures, cognitive interviews, and pilot testing. Seven questionnaire items were developed to measure synergy arising from equitable partnerships bringing together diverse partners across power differences to promote equity. Defining and measuring synergy in the context of long‐standing partnership success is central to understanding the role of synergy in collaborative approaches to research and action and can strengthen CBPR partnerships to promote healthy communities and advance health equity. Highlights: Synergy—accomplishing more together than alone—is central to effective collaborative partnerships. Measures of synergy specific to long‐standing equity‐focused CBPR partnerships are lacking. We developed a 7‐item measure integrating knowledge from community‐academic CBPR and equity experts. Evaluating synergy can strengthen CBPR partnership effectiveness to address health inequities. Fostering synergy will enhance CBPR partnership success to promote community health and equity.